Calvinism in the Polish-Lithuanian Commonwealth 548-1648 : the churches and the faithful - Bem, Kazimierz (St. Andrews studies in Reformation history., 2020)
Calvinism in the Polish-Lithuanian Commonwealth 1548-1648 offers an in-depth history of the Reformed Churches in the Polish-Lithuanian Commonwealth in its first hundred years. Dr. Kazimierz Bem analyses church polity, liturgy, the practices of Calvinist church discipline and piety, and the reasons for conversion to and from Calvinism in all strata of the society. It offers a detailed history of the three Reformed Churches. Drawing on extensive research in primary sources, Dr. Bem challenges the dominant narrative of Protestant decline after 1570 and argues for a continued flourishing of Calvinism in the Commonwealth until the 1630s.